Washback Effects: A Systematic Review of the Impact of Exit Exams on Teaching Strategies in Higher Education - Teshome, Samson Worku (International Journal of Education, Management, and Technology, 2025)
Exit exams in higher education have become a critical focus of educational policy and research, particularly regarding their influence on teaching strategies. This systematic review examines the impact of exit exams on teaching methodologies using the PRISMA framework to ensure rigor and transparency. By synthesizing evidence from 15 peer-reviewed articles, case studies, and reviews, this study identifies key themes such as curriculum alignment, teacher behavior, student engagement, institutional policies, and washback effects. The findings reveal that exit exams can lead to both positive and negative impacts on teaching strategies, depending on factors like exam design, stakeholder expectations, and resource availability. Positive outcomes include improved accountability, standardization, and alignment with industry standards, while negative consequences include "teaching to the test" and reduced opportunities for creative thinking. Contextual factors play a significant role in determining the effectiveness of exit exams. This review highlights the need for balanced approaches that integrate exit exams with broader educational goals. Policymakers, educators, and researchers are encouraged to collaborate in designing exit exams that enhance rather than hinder quality education. Future research should explore longitudinal impacts and innovative strategies to mitigate adverse effects.